A Deeper Look at the “Neural Correlate of Consciousness” - Fink, Sascha Benjamin (Frontiers in Psychology, 2016)
A main goal of the neuroscience of consciousness is: find the neural correlate to conscious experiences (NCC). When have we achieved this goal? The answer depends on our operationalisation of “NCC”. David Chalmers (2000) shaped the widely accepted operationalisation according to which an NCC is a neural system with a state which is minimally sufficient (but not necessary) for an experience. A deeper look at this operationalisation reveals four ways how it might be unsatisfactory: (i) it is not an operationalisation of a correlate of currently experiencing, but of the capacity to experience; (ii) it is impractical and unhelpful for certain cases which are sometimes used to motivate a search for neural correlates of consciousness; (iii) it does not mirror the usage of “NCC” by scientists who seek for unique correlates; (iv) it hardly allows for a form of comparative testing of hypotheses, namely experimenta crucis. If problems (i)–(iv) are unsatisfactory enough, then we ought to amend or improve on Chalmers’s operationalisation. Here, I present an alternative which avoids these problems. This “NCC2.0” also retains some benefits of Chalmers’s operationalisation, namely being compatible with contributions from extended, embedded, enacted, or embodied accounts (4E-accounts) and allowing for the possibility of non-biological or artificial experiencers.